2021
DOI: 10.1002/hed.26871
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pharyngeal motor function using a novel velopharyngeal squeeze maneuver and a novel endoscopic pharyngeal contraction grade scale in patients with dysphagia after radiotherapy for nasopharyngeal carcinoma

Abstract: Background To investigate a novel velopharyngeal squeeze maneuver (VPSM) and novel endoscopic pharyngeal contraction grade (EPCG) scale for the evaluation of pharyngeal motor function. Methods During endoscopic examination of 77 post‐irradiated nasopharyngeal carcinoma patients and control subjects, VPSM was rated and lateral pharyngeal wall movement graded with EPCG scale during swallowing. Pharyngeal constriction ratio (PCR) measured by videofluoroscopy was used for correlation. Results VPSM and EPCG scale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
(76 reference statements)
3
9
0
Order By: Relevance
“…Prior studies that demonstrated worsening PCR tend to have a median follow-up of 6 to 14 years from treatment, suggesting that PCR changes are more evident in late radiation associated dysphagia. 38,39 Similarly, PESmax did not change significantly in this study, which is consistent with previous research in OPSCC suggesting no differences when compared to controls 6 and 12 months following radiation. 6,36 Results from this study in conjunction with prior literature suggest PCR and PESmax may not significantly change in the first 2 years after treatment, however, long-term surveillance is critical.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Prior studies that demonstrated worsening PCR tend to have a median follow-up of 6 to 14 years from treatment, suggesting that PCR changes are more evident in late radiation associated dysphagia. 38,39 Similarly, PESmax did not change significantly in this study, which is consistent with previous research in OPSCC suggesting no differences when compared to controls 6 and 12 months following radiation. 6,36 Results from this study in conjunction with prior literature suggest PCR and PESmax may not significantly change in the first 2 years after treatment, however, long-term surveillance is critical.…”
Section: Discussionsupporting
confidence: 92%
“…Although mean PCR worsened in the study cohort, significance was lost after sex and age matching. Prior studies that demonstrated worsening PCR tend to have a median follow‐up of 6 to 14 years from treatment, suggesting that PCR changes are more evident in late radiation associated dysphagia 38,39 . Similarly, PESmax did not change significantly in this study, which is consistent with previous research in OPSCC suggesting no differences when compared to controls 6 and 12 months following radiation 6,36 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Dysphagia refers to swallowing problems caused by the impaired structure and function of swallowing organs, which often happens to patients with head and neck malignant tumors after treatment, such as NPC, laryngeal cancer, and tongue cancer [ 15 , 16 ]. As the most prevalent head and neck cancer in China [ 17 ], high-dose radiotherapy is preferred for NPC.…”
Section: Discussionmentioning
confidence: 99%